2008
DOI: 10.1093/brain/awn012
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype variability in progranulin mutation carriers: a clinical, neuropsychological, imaging and genetic study

Abstract: Frontotemporal dementia (FTD), characterized by behavioural and language disorders, is a clinically, genetically and pathologically heterogeneous group of diseases. The most recently identified of the four known genes is GRN, associated with 17q-linked FTD with ubiquitin-immunoreactive inclusions. GRN was analysed in 502 probands with frontal variant FTD (fvFTD), FTD with motoneuron disease (FTD-MND), primary progressive aphasia (PPA) and corticobasal degeneration syndrome (CBDS). We studied the clinical, neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
155
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(165 citation statements)
references
References 55 publications
8
155
0
2
Order By: Relevance
“…White matter changes such as gliosis and demyelination have long been observed in histological studies of FTD (Englund & Brun, 1987) and several groups have observed significant WMH on MRI brain scans of GRN mutation carriers with FTD who lack vascular risk factors (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017). However, studies that have characterized in detail the pathological correlates of WMH in GRN mutation associated FTD have until now been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…White matter changes such as gliosis and demyelination have long been observed in histological studies of FTD (Englund & Brun, 1987) and several groups have observed significant WMH on MRI brain scans of GRN mutation carriers with FTD who lack vascular risk factors (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017). However, studies that have characterized in detail the pathological correlates of WMH in GRN mutation associated FTD have until now been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, WMH are less commonly seen in frontotemporal dementia (FTD). Several studies have now reported prominent WMH in patients with familial FTD due to progranulin ( GRN ) mutations (Caroppo et al, 2014; Ameur et al, 2016; Kelley et al, 2009; Le Ber et al, 2008; Paternicò et al, 2016; Pietroboni et al, 2011; Sudre et al, 2017) but the pathological changes underlying these have not previously been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The other 2 familial nfvPPA cases presented the expanded hexanucleotide C9ORF72 mutation. Language dysfunction, nfvPPA or mixed PPA is a common presentation of GRN mutations [44]. The frequency of language disturbances at onset in C9ORF72 mutation carriers is variable across series, with 9–27% of patients presenting with nfvPPA [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism from which PGRN haploinsufficiency determines TDP-43 inclusions and, subsequently, brain damage and the clinical onset of disease is unknown. The behavioral (bvFTD) and the progressive nonfluent aphasia (PNFA) variants of FTLD are the most typical presentations in GRN mutation carriers, with a clinical onset in the 5th and 6th decades of life (LeBer et al, 2008;Masellis et al, 2006;Rademakers et al, 2007;Snowden et al, 2006;Van Deerlin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%